Cardiac Muscle Remodeling After Therapeutic Hypothermia and Allogeneic Mesenchymal Stromal Cells in a Model of Myocardial Infarction - Chizh, Mykola; Manchenko, Anna; Trofimova, Hanna; Belochkina, Irina (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 284